Vietnam's strategic engagement in the South China Sea. (2nd January 2021) - Sangtam, Apila
ABSTRACT: The rising tension between China and Vietnam with regard to the South China Sea has revised Hanoi's approach to its national defence policy. No longer benign and mute, it is taking an assertive stance and vocalising its opposition to the historical claims of Beijing. Hanoi is also becoming much more open to American presence in the South China Sea. This article examines the impact of geostrategic competition in the South China Sea on United States (US)–Vietnam and Indo-Vietnam bilateral relations, providing Hanoi an opportunity to challenge Beijing's illegal claims in the region.